The dynamics of the relationship between customer commitment and word-of-mouth advertising, the intention to stay, and the desire to pay a bonus through the interactive role of the company’s mental image - an analytical study of the opinions of a sample o: دراسة تحليلية لأراء عينة من زبائن شركة أسيا سيل - Hussein Ali Abdul Rasool; Elham Nemeh Kazem (Iraqi Journal for Administrative Sciences, 2024)
The present study aims to frame a customer-related model by investigation the impact of the customer's commitment to word of mouth, intention to stay, the willingness to pay, and impact the affective commitment to calculative commitment and normative commitment, and then to reinforce this relationship through the interactive role of the corporate image . A sample of 525 subscribers was selected from Asia Cell customers. Using the customer survey questionnaire, the data were analyzed by modeling the structural equation. An additional analysis was used to verify the interactive role of the image, which is the multi-regression regression analysis method. The results of the study indicate that affective commitment is the most important dimension that motivates customers to spread word of mouth, intention to stay, and willingness to pay. The impact of affective commitment on calculative commitment and normative commitment. The results showed that the company's image could strengthen those relationships. The study recommended improving the relationship of the company with customers who have a willingness to maintain the relationship with the company through the use of customer profitability analysis programs.